A systematic review of the epidemiology of unrecorded alcohol consumption and the chemical composition of unrecorded alcohol. (3rd March 2014) - Rehm, Jürgen; Kailasapillai, Shalini; Larsen, Elisabeth; Rehm, Maximilien X.; Samokhvalov, Andriy V.; Shield, Kevin D.; Roerecke, Michael; Lachenmeier, Dirk W.
Abstract Background and Aims Unrecorded alcohol constitutes about 30% of all alcohol consumed globally. The aims of this systematic review were to determine the epidemiology (occurrence, types, prevalence) of unrecorded alcohol consumption in different countries/regions, analyse the chemical composition of unrecorded alcohol and examine health outcomes caused by the consumption of unrecorded alcohol, based on either epidemiology or toxicology. Methods A systematic search for, and qualitative analysis of, papers with empirical results on the different categories of unrecorded alcohol, based on Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Results Unrecorded alcohol was widespread in all regions of the world. Artisanal fermented beverages and spirits were the most common categories of unrecorded alcohol globally, and were available on all continents. In India, industrially produced spirits (country spirits) were most prevalent. In Russia and countries of the former Soviet Union, surrogate alcohols complemented artisanal spirits. Cross‐border shopping was the most prevalent method of obtaining unrecorded alcohol in parts of Europe. Ethanol was the most harmful ingredient of unrecorded alcohol, and health consequences due to other ingredients found in unrecorded alcohol were scarce. However, as unrecorded alcohol is usually the least expensive form of alcohol available in many countries, it may contribute to higher rates of chronic and irregular heavy drinking. Conclusions Very large amounts of alcohol are produced globally that go unrecorded. The primary harm from this kind of alcohol arises from the fact that it is typically much cheaper than licit alcohol.